Centang “Bissa” dan Pa’Jaga Masiji : Pemberdayaan Masyarakat dalam Peningkatan Kepatuhan Protokol Kesehatan untuk Pencegahan dan Pengendalian Covid-19 - Anggraeni, Ike; Muhidin, Muh. Azmi; Ramadhani, Alfina Suci (Universitas Nusantara PGRI Kediri, 2022)
The implementation of health protocols is important as an effort to prevent Covid-19 transmission. However, its implementation in various community activities has not been optimal. A similar phenomenon was also found in Bukit Harapan Village, North Kalimantan. Observations and data survey and information result revealed that most people still do not care about using masks and washing hands either in general activities or worship activities. Thus it needed to change people's behavior which plays an important role in Covid-19 spreading. For this reason, community service is needed through community empowerment which is a part of health promotion strategy to mobilize the community to improve health behavior. Community service wass carried out through: (1) Centang